Robson 10-groups classification system to access C-section in two public hospitals of the Federal District/Brazil. - Cláudia Vicari Bolognani; Lílian Barros de Sousa Moreira Reis; Adriano Dias; Iracema de Mattos Paranhos Calderon (PLoS ONE, 2018)
The global increase in C-section rates is real. In Brazil, these indices correspond to 58.94% in the Midwest region and 52.77% in the Federal District.To evaluate the C-section rates and identify the groups with the greatest risk at two reference hospitals in the public network of Federal District/Brazil, using 10-Group Robson System.A cross-sectional study of 6579 births assisted at the Hospital A (HA) and the Hospital B (HB) during 2013. The C-section rates in each group and its respective contribution to the total hospital C-sections was compared between HA and HB. To this, was used the proportion difference test (similar to chi-square test), with RR and 95% CI, and the logistic regression analysis (OR; 95% CI) among the groups with higher C-section/total C-section. The significance limit of p < 0.05 was defined for all tests.The C-section rates were 50.8% at the HA and 42.3% at the HB, with 1.20 RR (95%CI = 1.13-1.28) at the HA. The highest rates were observed in Robson groups G5, G1, and G2. At the HA, G1 had a 21.5% C-section rate, which was greater than at the HB (13.8%; p < 0.05); the cesarean rates for groups G2 and G5 were higher at the HB (respectively, 18.6 and 38.1%) than at the HA (14.8 and 32.5%, respectively; p < 0.05).These results point out specific goals to be achieved in order to reduce abusive cesarean rates in both A and B hospitals, especially in the primigravida and in those with previous C-section.